Identification of Rub and Unbalance in 320-MW Turbogenerators - N. Bachschmid; P. Pennacchi; A. Vania; G. A. Zanetta; L. Gregori (International Journal of Rotating Machinery)
This article presents two experiences of application of a model-based fault identification method on real machines. The first case presented is an unbalance identification on a 320-MW turbogenerator unit operating in a fossil power plant. In the second case, concerning a machine of the same size but of a different manufacturer, the Low Pressure (LP) turbine was affected by a rub in the sealings and this time, the fault was modeled by local bows. The identification of the faults is performed by means of a model-based identification technique in frequency domain, suitably modified in order to take into account simultaneous faults. The theoretical background of the applied method is briefly illustrated and some considerations also are presented about the best choice of the rotating speed set of the run-down transient to be used for an effective identification and about the appropriate weighting of vibration measurements at the machine bearings.